Unusual Presentation Of Tracheoesophageal Fistula With Meconium Aspiration Syndrome In A Preterm Infant - Laraib Malik; Sina Aziz; Sadiq Mirza; Maria Khan (Journal of Digestive Disorders And Diagnosis, 2017)
Congenital malformations usually occur during organogenesis and result in complete or partial absence of an anatomical part or alteration in its normal configuration. Major structural anomalies occur in 2-3% of live births.The reported global incidence of tracheoesophageal fistula is roughly 1 in 2,500 live births and in Pakistan, incidence is only reported by those tertiary care centers which have paediatric surgery facilities available.We report a case of esophageal atresia (OA) with tracheoesophageal fistula (TEF) associated with meconium aspiration syndrome (MAS) in an infant. Reporting this anomaly highlights the importance of early diagnosis and thorough clinical examination of a newborn, signifying that a meticulous prenatal workup should be conducted. TEF/OA should be suspected in any newborn presenting with respiratory distress, especially cough, emesis and/or cyanosis during feeds, history of polyhydrominos and inability to pass nasogastric tube. The parents should also be counseled regarding future pregnancies as it carries a 1% risk of recurrence.
Keywords: Tracheoesophageal fistula